Pengaruh Pemahaman dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Restoran Di Kota Palu - Asrabiya; Jamaluddin; Ernawaty Usman (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of taxpayer understanding and awareness on restaurant tax compliance in Palu City. The population studied were restaurant taxpayers in the Palu City area. The data collection method used was a survey by distributing questionnaires to respondents met by researchers. The number of respondents in this study was 56 people. The data analysis technique used was multiple linear regression analysis with the help of SPSS software. The results of the study showed that taxpayer understanding and awareness had a positive and significant effect on restaurant tax compliance in Palu City.